Lipoprotein(a) among normotensive patients and risk of incident hypertension - Alexander R. Zheutlin; Joshua A. Jacobs; Brian Stamm; Regina Royan (The Journal of Clinical Hypertension)
Abstract Lipoprotein(a) has been shown to be disruptive to local endothelial cells, whose integrity is critical to blood pressure (BP) regulation. Cross‐sectional analysis has shown an association between lipoprotein(a) and prevalent hypertension, though it is unclear if lipoprotein(a) increases risk of incident hypertension. To assess this, the authors measured baseline lipoprotein(a) among 5307 normotensive patients (median age 26 years (interquartile range [IQR] 12–50) and used Cox proportional hazard models to generate hazard rations (HR) with 95% confidence intervals (CI; median follow‐up 10‐years). The authors categorized lipoprotein(a) as <15 mg/dL, 15–<30 mg/dL, 30–50 mg/dL, >50 mg/dL, and performed subgroup analysis of adults >50 years at baseline. Incident hypertension was defined as a measured BP ≥140/90 mm Hg or a new ICD‐9/10 code. After adjustment, hypertension for patients with baseline lipoprotein(a) 15–<30 mg/dL, 30–50 mg/dL, and >50 mg/dL was 0.91 (0.72–1.16), 1.05 (0.79–1.38), and 1.02 (0.83–1.26; vs. <15 mg/dL). However, among adults >50 years, lipoprotein(a) >50 mg/dL was associated with increased incident hypertension (1.62 [1.17–2.26]).